Analisis Faktor-Faktor Yang Dengan Perubahan Tekanan Darah Pada Ibu Hamil Di Wilayah Kerja Puskesmas Kertapati Palembang Tahun 2017 - Wahyuningsih, Retno (IKEMAS: Jurnal Ilmu Kesehatan Masyarakat, 2018)
One type of land transportation that is in demand by the public is the train. The railways not only have a positive impact on the surrounding community, but also the possible negative impacts of air pollution due to noise and vibration. This situation will greatly affect the health of the people living around the railroad tracks. The risk of people living on the railroad tracks is hearing the noise of the passing train along with its vibrations. Noise generated by trains can cause many health problems for people living nearby, whether physical or psychic. This study aims to determine the factors related to blood pressure in pregnant women in the vicinity of the Train Track in the Working Area of Kertapati Palembang Health Center in 2017. This research is a descriptive analytic survey with cross sectional approach. The study population is all pregnant women who live around the railway track in the working area of Puskesmas Kertapati. The sample of this research is as many as 32 people. From the amount, it can be concluded that the sampling method is total sampling. Technique of taking data using questioner. Data analysis with univariate, bivariate and multivariate analysis with multiple logistic regression method. The result of univariate analysis, there are 81,3% younger respondent, age 62,3%, distance of home is 59,4%, old population 53,1%, not smoking 78,1%, do not consume coffee 59.4%, and normal blood pressure as much as 75%. The result of bivariate analysis showed that there was no relationship for the variable of stay and work (p value> 0,05). The result of multivariate analysis got age which influence blood pressure of pregnant mother.